2014
DOI: 10.1186/1710-1492-10-14
|View full text |Cite
|
Sign up to set email alerts
|

Influence of the programmed cell death of lymphocytes on the immunity of patients with atopic bronchial asthma

Abstract: BackgroundFairly recent data highlight the role of programmed cell death and autoimmunity, as potentially important factors in the pathogenesis of chronic obstructive airway diseases. The purpose of our research was to determine the influence of apoptotic factors on the immunity of patients with atopic bronchial asthma according to the degree of severity.MethodThe study was performed on the peripheral blood of patients with atopic bronchial asthma with different severity. The Immunological aspects were determi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 33 publications
0
3
0
2
Order By: Relevance
“…Researchers have again come back to CIC analysis in patients with respiratory diseases. It has been published that there is a significant increase in the concentration of CIC in the blood of asthmatic patients (with atopic bronchial asthma) compared with controls [ 15 ], and also in COPD patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have again come back to CIC analysis in patients with respiratory diseases. It has been published that there is a significant increase in the concentration of CIC in the blood of asthmatic patients (with atopic bronchial asthma) compared with controls [ 15 ], and also in COPD patients [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…12 Two recent studies reported naturally occurring circulating anti-IgE IgG in healthy subjects, with increased titers in atopic and nonatopic asthmatic patients, 13 along with increased circulating immune complexes in the sera of asthmatic subjects with heightened disease severity. 14 To date, an autoimmune mechanism triggered locally in the lungs targeting eosinophil-specific antigens to explain asthma severity has not been investigated. According to our hypothesis of a degranulation-mediated increase in immunogenic entities in the airways, we aimed to investigate the presence of autoantibodies targeted against EPX and autologous cellular/nuclear material (ie, ANAs) to further assess the possibility of a localized polyclonal autoimmune event associated with asthma severity.…”
mentioning
confidence: 99%
“…Notably, apoptosis is one form of programmed cell death. In addition, early programmed cell death of lymphocytes destroys innate and adaptive immunity, which would reduce the ability of protecting against pathogens (49). Also, programmed cell death of parenchymal cells in the lung, liver and gut would facilitate organ failure and death (50).…”
Section: Discussionmentioning
confidence: 99%